Infantile mucocutaneous leishmaniasis: an emerging disease in Venezuela. - Ramirez, J.L.; Premoli de Percoco, G.; Guevara, P.; Castellanos, A.; Belfort, E. (European Journal of Pediatric Dermatology, 2000)
We here present a pediatric case of cutaneous leishmaniasis with a concomitant involvement of the nasal and palate mucosa. The diagnosis of the disease was difficult, and its evolution atypical. This topic is discussed also to underline the emerging cases of pediatric leishmaniasis and the lack of proper attention to teaching of tropical medicine in endemic areas.